Vegetable cultivation as a diversification option for fruit farmers in the Goulburn Valley, Australia. Issue 1 (2nd January 2022) - Gupta, Dorin; Davidson, Brian; Hill, Megan; McCutcheon, Aimee; Pandher, Malwinder Singh; MacDonald, Darla Hatton; Hamilton, Andrew John; Mekala, Gayathri Devi
ABSTRACT: Worldwide, water scarcity, profit-cost pressure and restructuring of agricultural markets have led to on-farm diversification. The Goulburn Valley's (GV) pome and stone fruit farms, in the Murray-Darling Basin of Australia, present potential lessons for the conditions under which alternative crops can sustain livelihoods. This research uses a mixed methods approach to assess the viability of vegetable production in the GV region. Quantitative and qualitative data collected from primary and secondary sources were analysed within the conceptual framework of 'opportunity and ability to diversify'. The favourable biophysical factors of GV region and a positive return on investment from vegetable production that is comparable with fruit production, provide an opportunity for crop diversification to the fruit farmers of the region. Socio-economic factors, including loss of market for fruit crops, family and peer group support and flexibility in vegetable production, supported crop diversification. Factors that prevented fruit growers from diversification include, risk to existing business, capital locked in fruit related infrastructure and lack of vegetable marketing knowledge, among other reasons. The approach highlights the underlying factors for crop diversification that can be applied to any region by agricultural extension agencies to evaluate the potential for diversification.